2001
DOI: 10.2183/pjab.77.19
|View full text |Cite
|
Sign up to set email alerts
|

Large low frequency dielectric constant exhibited by hydrated rock materials

Abstract: Abstract:The dielectric properties of low porosity polycrystalline marble and granite rocks were investigated using broadband dielectric relaxation spectroscopy (10-2-106 Hz) at fixed room temperature (295 K) . The water content of the specimens was varied between 0 and 0.22 % (mass of absorbed water per mass of dry rock material %). The dielectric relaxation spectra were found to exhibit large low-frequency dispersion that depends strongly on the water content. A thorough study of this dispersion reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The dielectric permittivity of a three-phase medium plays the most important role in determining n. Considering that the dielectric permittivity is 1 for air, approximately 3 to 6 for solid particles and 81 for water, the value of ε r for a given medium is strongly influenced by the moisture content (Kyritsis et al, 2001;Sengwa and Soni, 2006).…”
Section: Dielectric Permittivitymentioning
confidence: 99%
“…The dielectric permittivity of a three-phase medium plays the most important role in determining n. Considering that the dielectric permittivity is 1 for air, approximately 3 to 6 for solid particles and 81 for water, the value of ε r for a given medium is strongly influenced by the moisture content (Kyritsis et al, 2001;Sengwa and Soni, 2006).…”
Section: Dielectric Permittivitymentioning
confidence: 99%
“…5, which both sides covered with Au ion blocking electrodes (cf. for the meaning of the quantities used in this plot, see for example [18] and [19]). The contributions due to bulk (b) and grain-boundary (gb) effects were observed at high and low frequencies, respectively.…”
Section: Characterization Of Electrolyte and Auxiliary Layermentioning
confidence: 99%
“…In the past decades, many applications extensively confirmed that electromagnetic pulse propagation is strongly dependent on the dielectric properties of materials that are generally described by the dielectric permittivity. Considering that the dielectric constant is 1 for air, approximately 3 to 6 for solid particles, and 81 for water, the value of the dielectric constant is strongly influenced by the water content [15][16][17][18][19]. The internal relationshipsand models between dielectric constant and water content have been an major task in GPR field application since last century, among which velocity of propagation of GPR signals should be assumed a priori [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%